THE EFFECT OF THE READING GUIDE MODEL ON STUDENTS’ READING COMPREHENSION SKILLS IN ELEMENTARY SCHOOL - Vevy Liansari (Academic Journal Research, 2026)
Objective: This study aims to determine the effect of the Reading Guide learning model on the reading comprehension skills of elementary school students. The study is based on the need for twenty-first century learning approaches that can improve students’ critical thinking and literacy skills, considering that Indonesian students’ reading abilities are still relatively low according to PISA and PIRLS results. Method: This study employed a pre-experimental research method using a One-Group Pretest–Posttest design. The participants were 22 fifth-grade students of SDN Gedangan. Data were collected through written tests administered before and after the implementation of the Reading Guide model. The collected data were analyzed by comparing students’ pretest and posttest scores to measure the improvement in reading comprehension skills. Results: The findings showed that students’ posttest scores were significantly higher than their pretest scores. The implementation of the Reading Guide model effectively improved students’ reading comprehension skills by helping them focus on reading materials, identify important information, and actively participate in learning activities through guided questions and reflective discussions. Novelty: This study contributes to the development of literacy-based learning strategies in elementary education by emphasizing the effectiveness of the Reading Guide model as a systematic and interactive approach to improving reading comprehension skills among elementary school students.